2019
DOI: 10.1002/dev.21944
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress and development of the endocannabinoid system: A bidirectional process in programming future coping

Abstract: The endocannabinoid system (ECS) critically regulates stress responsivity and emotional behavior throughout development. It regulates anxiety‐like behaviors in humans and animal models. In addition, it is sensitive to early life stress at the gene expression level in a sex‐dependent and region‐dependent manner, and these changes are already evident in the adolescent brain. The ECS modulates the neuroendocrine and behavioral effects of stress, and is also capable of being affected by stress exposure itself. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 148 publications
(183 reference statements)
1
18
0
1
Order By: Relevance
“…Both clinical and experimental studies have shown that ELS affects the eCB system and increases the risk of psychopathologies, such as addiction and depression [for review, see (Goldstein Ferber et al., 2019)]. Our current results indicated that the rewarding properties of CB1R agonist decreased in the MS.…”
Section: Discussionsupporting
confidence: 50%
“…Both clinical and experimental studies have shown that ELS affects the eCB system and increases the risk of psychopathologies, such as addiction and depression [for review, see (Goldstein Ferber et al., 2019)]. Our current results indicated that the rewarding properties of CB1R agonist decreased in the MS.…”
Section: Discussionsupporting
confidence: 50%
“…For instance, mice exposed to maternal separation showed decreased CB1-R binding site densities within the amygdala, in both adolescence and adulthood. By contrast, alterations in the concentration of AEA and 2-AEG were only documented in infant rats after maternal separation stress [71,72] (Figure 3).…”
Section: Stress Exposure During the Perinatal Period: Perinatal Stressmentioning
confidence: 94%
“…Note that regions involved in the stress reaction are compromised by glucocorticoid mediated atrophy (i.e., hippocampus, PFC) [146] and they are also key regulators of mesolimbic and mesocortical dopaminergic pathways [145] indirectly affecting the reward circuits. The ECS is affected by stress and it only partially recovers with positive inputs [129]. However, recent reports show that the ECS, especially the CB1R, buffers the detrimental impact of stress on reward sensitivity [147,148].…”
Section: Vulnerability Of Dopamine and Endocannabinoid Systems Withinmentioning
confidence: 98%
“…Due to the potential of the endocannabinoid receptors to increase sensitivity to a reward in the behavioral and neural levels, their location within the reward circuits is crucial for cases of major depression lacking this sensitivity and pro-hedonic behavior related to it [127]. Recently, we discussed the epigenetic fragility of the ECS [128] and the bidirectional function of the system under stress [129]. Moreover, histone deacetylase (HDAC) inhibitors were found to interact with the ECS on the epigenetic level in preclinical studies of depression and chronic stress effects [130,131], suggesting that the crosstalk between ECS and DA receptors may be located at the epigenetic level.…”
Section: The Endocannabinoid System and Major Depressionmentioning
confidence: 99%